Decline in acute coronary syndrome hospitalisation rates during COVID-19 lockdown in private hospitals in South Africa - Delport, R; Vachiat, A; Snyders, A; Kettles, D; Weich, H (SA Heart Journal, 2020)
We conducted a study of admission rates of acute coronary syndrome (ACS) in all Mediclinic hospitals in South Africa. The aim of the study was to quantify the extent of change in admission rates of ACS subtypes and to establish the degree of change in subtype proportions in the private sector assumed to be related to COVID-19 and/or lockdown implementation. Time intervals were demarcated by lockdown measures (March: pre-lockdown versus April: post-lockdown implementation), and comparisons were performed with equitable time periods (2019 versus 2020). For the comparison of proportions, data for April and May were summated.